A constructional approach to interpersonal metaphor of modality - Hu, Jian (Peking University linguistics research, 2023)
This book is a current and comprehensive study that incorporates constructional frameworks to inquire grammatical metaphor of modality (MM) for more adequate description and explanation of grammatical metaphor. It conducts semantic analysis of MM via a refined cognitive model and investigation of its lexicogrammatical forms from corpus-based constructional approach. The result is a reliable and systemic record of MM in real use, coupled with theoretical refinement from a cognitive perspective to illuminate its ‘metaphoricity’ motivation. The constructional approach and methodology exemplified in this book provide fresh insights, rich data, and a feasible solution for the adequate description and explanation of grammatical metaphor phenomena and the form-meaning interactive complexity in modality